Upregulation of Glutamic-Oxaloacetic Transaminase 1 Predicts Poor Prognosis in Acute Myeloid Leukemia - Cheng, Zhiheng; Dai, Yifeng; Zeng, Tiansheng; Liu, Yan; Cui, Longzhen; Qian, Tingting; Si, Chaozeng; Huang, Wenhui; Pang, Ying; Ye, Xu; Shi, Jinlong; Fu, Lin (Frontiers in Oncology, 2020)
One of the key features of acute myeloid leukemia (AML), a group of very aggressive myeloid malignancies, is their strikingly heterogenous outcomes. Accurate biomarkers are needed to improve prognostic assessment. Glutamate oxaloacetate transaminase 1 (GOT1) is essential for cell proliferation and apoptosis by regulating cell's metabolic dependency on glucose. It is unclear whether the expression level of GOT1 has clinical implications in AML. Therefore, we analyzed the data of 155 AML patients with GOT1 expression information from The Cancer Genome Atlas (TCGA) database. Among them, 84 patients were treated with chemotherapy alone, while 71 received allogeneic hematopoietic stem cell transplantation (allo-HSCT). In both treatment groups, high GOT1 expression was associated with shorter event-free survival (EFS) and overall survival (OS) (all P < 0.05). Multivariate analysis identified several independent risk factors for both EFS and OS in the chemotherapy-only group, including high GOT1 expression, age ≥60 years, white blood cell count ≥15 × 109/L, bone marrow blasts ≥70%, and DNMT3A, RUNX1 or TP53 mutations (all P < 0.05); but in the allo-HSCT group, the only independent risk factor for survival was high GOT1 expression (P < 0.05 for both EFS and OS). Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that the genes related to GOT1 expression were mainly concentrated in “hematopoietic cell lineage” and “leukocyte transendothelial migration” signaling pathways. Collectively, GOT1 expression may be a useful prognostic indicator in AML, especially in patients who have undergone allo-HSCT.